THE RELATIONSHIP BETWEEN RESILIENCE AND LEARNING MOTIVATION IN ADOLESCENTS WITH DIVORCED PARENTS - Lestari, Jaya; Jalal, Novita Maulidya; Rasyid, Nurfajriyanti (JURNAL NALAR PENDIDIKAN, 2024)
Situations and conditions of different family statuses, such as families with divorced status, make students who have this experience feel different from other students, providing challenges for each student who has this experience. This condition triggers obstacles and pressures during the learning process at school, so an ability that can be built into facing these problematic experiences is needed; this ability is resilience. This research aims to see and determine the relationship between resilience and learning motivation in adolescents whose parents are divorced. The subjects in this study consisted of 162 students from divorced parents at SMA Kartika XX-1 Makassar. The sampling technique used in this research was saturated samples. This research was measured using a modified learning motivation and resilience scale. The analysis used in this research is product-moment correlation using SPSS 26.0 software. The results of this study show that in adolescents whose parents are divorced, there is a relationship between resilience and learning motivation with a significance value of 0.000 (sig < α). The person correlation value is 0.994, which means that the higher the resilience, the higher the motivation to learn in teenagers whose parents are divorced. The implications of this research can provide an overview of resilience and learning motivation in adolescents whose parents are divorced